Neuroprotective and antioxidant activities of Colombian plants against paraquat and C2-ceramide exposure in SH-SY5Y cells - Bustos-Rangel, Angie; Muñoz-Cabrera, Jonathan; Cuca, Luis; Arboleda, Gonzalo; Ávila Murillo, Mónica; Sandoval-Hernández, Adrián G. (Frontiers in Natural Products, 2023)
Abnormal production of reactive oxygen species (ROS) has been implicated in the physiopathology of neuronal cell death. Increased ROS levels are associated with exacerbated peptide aggregation, inflammation, and mitochondrial dysfunction which facilitate the triggering of specific cell death pathways, then antioxidant molecules are potentially useful in the amelioration of neurodegeneration. In this regard, natural products are an invaluable source of antioxidants. Therefore, here we investigate the antioxidant and neuroprotective activity of four Colombian angiosperm extracts. Antioxidant activity was evaluated by phytochemical assays using TLC techniques with Dragendorff, ninhydrin, and chloranil in dioxane, NH3, Fast blue, and FeCl3, together with bioautography using DPPH and β-carotene. In vitro neuroprotective activity, cell death, and ROS accumulation was evaluated in the SH-SY5Y cell line exposed to Paraquat and C2-Con formato: Fuente: (Predeterminada) Arial, 12 pto ceramide by MTT and flow cytometry. We found that Zanthoxylum rhoifolium Lam, Zanthoxylum martinicense, Nectandra membranacea, and Nectandra reticulata extracts have antioxidants activity higher than quercetin under β-carotene bleaching assay, protect SH-SY5Y cells against Paraquat and C2-ceramide associated to a reduction in ROS. In conclusion, those extracts have a strong neuroprotective potential the precise mechanism requires more evaluation.